Determinants of photochemical characteristics of the photosynthetic electron transport chain of maize - Liu, Xiuping; Qiao, Yunzhou; Zhou, Wangming; Dong, Wenxu; Gu, Lianhong (Frontiers in Plant Science, 2023)
The photosynthetic electron transport chain (ETC) is the bridge that links energy harvesting during the photophysical reactions in one end and energy consumption during the biochemical reactions in the other. Its functioning is thus fundamental to the proper balance between energy supply and demand of photosynthesis. Currently there is a lack of knowledge regarding how the structural properties of ETC are affected by nutrient availability and plant developmental stages, which is a major roadblock for complete modeling of photosynthesis. Redox parameters reflect the structural controls of ETC on the photochemical reactions and electron transport. We conducted joint measurements of chlorophyll fluorescence (ChlF) and gas exchange under systematically varying environmental conditions and growth stages of maize and sampled foliar nutrient contents. We utilized the recently developed steady-state photochemical model to infer redox parameters of electron transport from these measurements. We found that the inferred values of these photochemical redox parameters varied with leaf macronutrient contents. These variations can be caused either directly by these nutrients being a component of protein complexes on the ETC or indirectly by their impacts on the structural integrity of thylakoid and feedbacks from the biochemical reactions. Also, the redox parameters varied with plant morphology and developmental stages, reflecting seasonal changes in the structural properties of the ETC. Our findings will facilitate the parameterization and simulations of complete models of photosynthesis.